2021
DOI: 10.1007/s13304-021-01136-x
|View full text |Cite
|
Sign up to set email alerts
|

An international multidisciplinary peer-driven consensus on the optimal use of hemostatic powders in surgical practice

Abstract: Bleeding is a consequence of insufficient hemostasis and excessive bleeding at a surgical site is associated with an increased risk of post-operative infection, transfusion and re-operation, in addition to increased hospital length of stay and costs. Surgeons employ a range of methods to achieve hemostasis, including topical hemostatic agents of differing composition and properties. Hemostatic powders are a sub-group of topical hemostats, which can be used in helping as adjuncts to manage troublesome bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…However, postoperative complications such as wound site infection or bleeding can often lead to discharge delays. While intraoperative control of bleeding remains pivotal for the reduction of postoperative complications, the application of topical hemostatic agents has become very common in the last two decades 18 . Specifically the effect of fibrin sealant containing human thrombin or combined hemostatic powder containing collagen, thrombin and chondroitin sulfate has been evaluated in the past, resulting in early drainage removal and increased day-case surgery 15,17,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, postoperative complications such as wound site infection or bleeding can often lead to discharge delays. While intraoperative control of bleeding remains pivotal for the reduction of postoperative complications, the application of topical hemostatic agents has become very common in the last two decades 18 . Specifically the effect of fibrin sealant containing human thrombin or combined hemostatic powder containing collagen, thrombin and chondroitin sulfate has been evaluated in the past, resulting in early drainage removal and increased day-case surgery 15,17,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications like bleeding, wound site infection or seroma formation are however still sources for morbidity and are associated with hospital readmission and high health care costs [3][4][5] . During surgery, a delicate balance between bleeding and clotting has to be reached, in order to maintain tissue perfusion and to avoid postoperative bleeding, infections or tissues necrosis 6 . Studies conducted on the murine model have shown neoangiogenesis and fibrosis in the wound site after the application of local hemostatic agents, with no significant increase of tissue inflammation or necrosis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In general, patients may be at increased risk of bleeding for advanced age, decreased preoperative red blood cell volume (small body size and/or preoperative anaemia), medications affecting haemostasis, including complementary medicines, medical conditions causing haemostatic defect such hereditary bleeding disorders and acquired medical conditions like chronic kidney or liver disease, and high-risk procedures [14]. Furthermore, risk factors in any kind of surgery are previous surgery and extended and multiorgan resections, while gender, body mass index, and comorbidities including arterial hypertension, diabetes mellitus and renal dysfunction are independent risk factors for bleeding and transfusion [14,15]. A recent large retrospective cohort study in patients undergoing caesarean myomectomy for intramural leiomyoma, showed that the large size and lower segmental position of the leiomyoma are significantly risk factors for intraoperative haemorrhage during caesarean myomectomy [16].…”
Section: Risk Factors For Perioperative Haemorrhagementioning
confidence: 99%
“…12 – 14 Due to their ease of application, these agents have been adopted for widespread use in both open and minimally invasive abdominal surgeries. 15 , 16 While PSP was approved by the FDA for use in the US in 2006 and FSS in 1998, ORC was developed more recently and approved for use in 2017. 12 , 13 , 17 As a relatively new product, there is limited information on AEs reported with use of ORC in the literature.…”
Section: Introductionmentioning
confidence: 99%